PEMODELAN LAJU KESEMBUHAN PASIEN RAWAT INAP TYPHUS ABDOMINALIS (DEMAM TIFOID) MENGGUNAKAN MODEL REGRESI KEGAGALAN PROPORSIONAL DARI COX (Studi Kasus di RSUD Kota Semarang) - Bellina Ayu Rinni; Triastuti Wuryandari; Agus Rusgiyono (Jurnal Gaussian, 2014)
Typhus Abdominalis (typhoid fever) is a systemic infectious disease caused by Salmonella typhi and ranked 3rd of 10 major inpatient diseases in the hospitals of Indonesia based on Indonesia’s health profile data in 2010. It's important to know the factors that can affect the rate of recovery of hospitalized patients suffering from typhoid fever. One way is to use survival analysis that is a statistical method to analyze survival data. Cox proportional hazards regression is a model in survival analysis used to determine the relationship between one or more independent variables and the dependent variable. This model does not require information about the underlying distribution, but the hazard functions of different individuals assumed to be proportional. The Data used are from 45 patients of thypoid fever on RSUD Kota Semarang who have been medically recorded from  August 1st 2012 until November 30st 2012. Furthermore it is concluded that the factors that affect the rate of recovery of inpatients suffering from typhoid fever were age.